RANCANG BANGUN SISTEM INFORMASI KLAIM KESEHATAN DAN PINJAMAN DANA BERBASIS WEB PADA PT. CITRA BANJAR ABADI - Fauziah Syifa R. Siregar (2022)
PT. Citra Banjar Abadi provides facilities to its employees aimed at improving the performance of employees of this company in the form of health claims and loan funds. But the process is done manually and not computerized so that there are still many errors that occur such as the long process of submitting and missing submissions. Therefore, the author makes a web-based information system design. In making the system, the author uses PIECES analysis in determining the system requirements according to the wishes of the user. In addition, the author uses the Waterfall method so that the system can run smoothly.